Koalisi Teritorial untuk Pembentukan Daerah Otonomi Baru di Indonesia Pasca Reformasi: Kegagalan Pembentukan Provinsi Luwu Raya 1999-2014 - Meliala, Fransiskus Chandra Dwiputra (Jurnal Review Politik, 2022)
The establishment of a new autonomous region is an implementation of the implementation of decentralization in Indonesia. Previous studies have shown that regional expansion in Indonesia is highly motivated by elite interests. Even so, not all regional expansion efforts can be successful. This article explains what caused the formation of the Luwu Raya Province to not materialize even though the political movement had emerged since 1999. This article finds two things: First, fragmentation of local elites in the province candidate areas has emerged since the beginning of the struggle for the formation of a new province. Second, there are obstacles made by political actors who try to hinder efforts to form the Luwu Raya Province Pembentukan daerah otonom baru merupakan implementasi  dari pemberlakuan desentralisasi di Indonesia. Studi-studi terdahulu telah menunjukkan bahwa pemekaran wilayah di Indonesia sangat dimotivasi oleh kepentingan elit. Walaupun begitu, tidak semua usaha pemekaran wilayah dapat berhasil. Artikel ini menjelaskan apa yang menyebabkan pembentukan Provinsi Luwu Raya tidak terwujud walaupun gerakan politiknya sudah muncul sejak tahun 1999. Artikel ini menemukan dua hal:Pertama, fragmentasi elit lokal di wilayah calon provinsi sudah muncul sejak awal perjuangan pembentukan provinsi baru. Kedua, adanya rintangan yang dilakukan oleh aktor politik yang berusaha menghalangi upaya pembentukan Provinsi Luwu Raya.